2020
DOI: 10.3390/nu12082275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Molecular Weight of Oat β-Glucan Taken just before Eating on Postprandial Glycemic Response in Healthy Humans

Abstract: To see if the molecular weight (MW) and viscosity of oat β-glucan (OBG) when taken before eating determine its effect on postprandial glycemic responses (PPRG), healthy overnight-fasted subjects (n = 16) were studied on eight separate occasions. Subjects consumed 200 mL water alone (Control) or with 4 g OBG varying in MW and viscosity followed, 2–3 min later, by 113 g white-bread. Blood was taken fasting and at 15, 30, 45, 60, 90, and 120 min after starting to eat. None of the OBG treatments differed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The ability of beta-glucan to reduce post-prandial glycemic response is well established ( 43 ) and has been ascribed viscosity formation in the intestine which is determined by dose, solubility under physiological conditions, and molecular weight ( 44 , 45 ). In the present study, both medium and high beta-glucan meals had beta-glucans with high molecular weight, but differences in dose and solubility (higher for high beta-glucan meal) resulted in a huge difference of viscosity after simulated digestion ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of beta-glucan to reduce post-prandial glycemic response is well established ( 43 ) and has been ascribed viscosity formation in the intestine which is determined by dose, solubility under physiological conditions, and molecular weight ( 44 , 45 ). In the present study, both medium and high beta-glucan meals had beta-glucans with high molecular weight, but differences in dose and solubility (higher for high beta-glucan meal) resulted in a huge difference of viscosity after simulated digestion ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to increase intestinal viscosity and consequently slow the rate of gastric emptying and the absorption of carbohydrate has the effect of decreasing the postprandial glycemic response to the carbohydrate contained in a meal 43. Systematic reviews and meta-analyses of acute RCTs have shown a strong linear relationship between reductions in postprandial glucose following a carbohydrate meal and an increase in the dose and molecular weight of ß-glucan 44 45. The alpha-glucosidase inhibitor acarbose provides important biological analogy as an oral prandial agent that effectively converts the diet to a low glycemic index (GI) diet by decreasing the absorption of the carbohydrate contained in a meal, thereby decreasing the acute postprandial glycemic response 46–49.…”
Section: Discussionmentioning
confidence: 99%
“…Wolever et al [ 134 ] confirmed the influence of oat β - d -glucans of various M w on PPGR; they found that a decrease in M w correlates with the time reduction for blood glucose to reach its peak, while HMW β - d -glucan demonstrated the opposite effect. Zurbau et al [ 135 ], analyzing data from 103 trials ( N = 538), found that oat β - d -glucans of different M w can affect important diabetes biomarkers such as postprandial blood glucose and insulin response dramatically.…”
Section: Anti-diabetic Activitiesmentioning
confidence: 97%